1987
DOI: 10.1111/j.1365-3083.1987.tb02313.x
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐Purification of an Immunosuppressor Substance Secreted by Streptococcus mutans that Plays a Role in the Protection of the Bacteria in the Host

Abstract: Crude extracellular products of Streptococcus mutans (CEP-Sm) suppress the proliferative response to phytohaemagglutinin of human peripheral blood mononuclear cells and the primary immune response of C57BL/6 mice to sheep erythrocytes. This immunosuppressive effect favours the survival of the microorganism, and the bacteria lose the ability to secrete immunosuppressor substance if previously subcultured several times. Cells incubated with CEP-Sm and subsequently washed recover the ability to proliferate. Trace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…They are immunomodulatory because they are simultaneously mitogens for T-and B-lymphocytes and immunosuppressive for foreign antigens (Arala-Chaves et Ferreira et al, 1988;Lima et al, 1992;Pal & Horwitz, 1992;Ribeiro et al, 1991;Soares et al, 1990;Tavares et al, 1993). We have shown the importance of VIPs for the survival of pathogenic micro-organisms to be due to the fact that they potentiate microbial growth (Lima et al, 1992;Santarem et al, 1987;Tavares et al, 1993) and because mice immunized with VIPs become resistant to infection (Soares et al, 1990;Tavares et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are immunomodulatory because they are simultaneously mitogens for T-and B-lymphocytes and immunosuppressive for foreign antigens (Arala-Chaves et Ferreira et al, 1988;Lima et al, 1992;Pal & Horwitz, 1992;Ribeiro et al, 1991;Soares et al, 1990;Tavares et al, 1993). We have shown the importance of VIPs for the survival of pathogenic micro-organisms to be due to the fact that they potentiate microbial growth (Lima et al, 1992;Santarem et al, 1987;Tavares et al, 1993) and because mice immunized with VIPs become resistant to infection (Soares et al, 1990;Tavares et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously observed that bacteria (Ferreira et al, 1997;Lima et al, 1992;Santarem et al, 1987), viruses and fungi (Tavares et al, 1993) secrete virulence-associated immunomodulatory proteins (VIPs). These VIPs are only produced by micro-organisms in their pathogenic form.…”
Section: Introductionmentioning
confidence: 99%
“…They induce polyclonal activation of lymphocytes, as well as the suppression of the host immune response to microbial specific antigens (8,19,39). It was also found that specific immunization against virulenceassociated immunomodulatory proteins (but not against other antigenic components of the microbe) induces immunoprotection (39,47). In a mouse model of Trypanosoma cruzi infection, a B-cell-mitogenic protein was isolated from the culture supernatants of the parasite infective forms.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that different pathogenic microorganisms produce mitogenic and immunosuppressive proteins which also constitute important virulence factors (7,8,18,19,39). Such proteins have been generally designated virulence-associated immunomodulatory proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation